Dr. Hansen on the Inflationary Gap: Further Comment - Paunio, J. J. (Review of Economic Studies, 1954)
Journal Article Dr. Hansen on the Inflationary Gap: Further Comment Get access J. J. Paunio J. J. Paunio Helsinki Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 22, Issue 2, 1954, Pages 151–152, https://doi.org/10.2307/2296289 Published: 01 January 1954